Association of Financial Literacy and Money Management Competence among Male and Female University Teachers of Karachi - Maryam, Madiha; Zehra , Nobia (Nurture, 2015)
This study aimed at finding “Association of financial literacy with money management competence among male and female university teachers of Karachi.” Two hundred university teachers participated in this study. Association of financial literacy with money management competence were found out through rank correlations. There was a weak but significant positive association between financial literacy and money management competence ( P=0.014, r=0.174). Enhancing public financial literacy can help in improving financial management competence and can lead to better quality of life